2020
DOI: 10.1371/journal.pone.0234353
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent epidural bolus versus continuous epidural infusions for labor analgesia: A meta-analysis of randomized controlled trials

Abstract: There are inconsistent results regarding the efficacy and safety of intermittent epidural bolus (IPB) versus continuous epidural infusions (CPI) for labor analgesia. This study used a meta-analytic approach to assess the safety and treatment efficacy of IPB versus CPI for labor analgesia based on randomized controlled trials (RCTs). Four electronic databases were used to identify eligible RCTs. Pooled effect estimates at 95% confidence intervals (CIs) were calculated using a random-effects model. Twenty-two RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Both obstetric and anaesthetic practice has changed during this time, with rates of assisted vaginal delivery falling [21] and caesarean section rates increasing 4% per year worldwide [22]. Evidence is accumulating supporting the use of intermittent bolus and patientcontrolled epidural analgesia rather than continuous epidural regimes to reduce the total dose of local anaesthetic given [23,24]. Reducing the concentration of local anaesthetic is a straightforward intervention that would be easy to unknown and this may be a key area for future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both obstetric and anaesthetic practice has changed during this time, with rates of assisted vaginal delivery falling [21] and caesarean section rates increasing 4% per year worldwide [22]. Evidence is accumulating supporting the use of intermittent bolus and patientcontrolled epidural analgesia rather than continuous epidural regimes to reduce the total dose of local anaesthetic given [23,24]. Reducing the concentration of local anaesthetic is a straightforward intervention that would be easy to unknown and this may be a key area for future work.…”
Section: Discussionmentioning
confidence: 99%
“…All methods of epidural maintenance were included in this meta-analysis. This may influence our results as there is evidence that women require lower total doses of local anaesthetic when using patient-controlled epidural analgesia, or intermittent bolus rather than continuous infusions [23,24]. However, only two of the studies used different methods of administration of epidural maintenance for different groups of the trial meaning that the variable being assessed was the local anaesthetic concentration rather than the method of administration [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in treatment efficacy between IEB and CEI for labor analgesia has been addressed in previous systematic reviews and meta-analyses [ 47 , 48 , 49 ]. In 2013, a well-conducted meta-analysis [ 47 ] of nine studies that showed minor reduction in local anesthetic usage and improvement of maternal satisfaction were related to receiving IEB.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, for the IEB with PCEA group, the results showed shorter labor duration and maternal satisfaction improvement compared to the CEI with PCEA group. The latest and final meta-analysis [ 49 ] recruited 22 RCTs with 2573 parturients. Among these meta-analyses, Liu et al evidently conducted a meta-analysis with the largest sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed intermittent epidural boluses (PIEB), a newly established technology, provides better analgesia, less motor block and lower local anesthetic drug consumption compared with traditional continuous epidural infusion (CEI), which has being used in labour analgesia. 18–21 Therefore, we hypothesized that PIEB may provide superior uterine contraction pain and incision pain relief and less motor block than CEI. Our primary aim was to evaluate the effectiveness of uterine contraction pain relief assessed with visual analog scale (VAS) score at the postoperative 36 h.…”
Section: Introductionmentioning
confidence: 99%